H/ACA snoRNP Gene Family as Diagnostic and Prognostic Biomarkers for Hepatocellular Carcinoma - Zhang M; Zhao W; Liu S; Liu H; Liu L; Peng Q; Du C; Jiang N (Dove Medical Press, 2021)
Mi Zhang,1 Wei Zhao,2 Shanshan Liu,1 Haichuan Liu,1 Liang Liu,2 Qiling Peng,2 Chengyou Du,1 Ning Jiang3 1Department of Hepatobiliary Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People's Republic of China; 2School of Basic Medical Science, Chongqing Medical University, Chongqing, 400016, People's Republic of China; 3Department of Pathology, Chongqing Medical University, Chongqing, 400016, People's Republic of ChinaCorrespondence: Chengyou Du; Ning Jiang Email duchengyou@126.com; jiangning@cqmu.edu.cnBackground: The H/ACA small nucleolar ribonucleoprotein (snoRNP) gene family, including GAR1 ribonucleoprotein (GAR1), NHP2 ribonucleoprotein (NHP2), NOP10 ribonucleoprotein (NOP10), and dyskerin pseudouridine synthase 1 (DKC1), play important roles in ribosome biogenesis. However, the potential clinical value of the H/ACA snoRNP gene family in hepatocellular carcinoma (HCC) has not yet been reported.Methods: Bioinformation databases were used to analyze the expression and roles of the H/ACA snoRNP gene family in HCC. Survival analysis, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes enrichment pathway (KEGG) analyses were performed using R software. Tumor Immune Estimation Resource (TIMER) was used to analyze the correlation between the expression of the H/ACA snoRNP gene family and immune infiltration in HCC. Finally, immunohistochemistry and Western blotting were performed to verify the protein expression of the H/ACA snoRNP gene family in HCC tissues and adjacent tissues.Results: The expression of the H/ACA snoRNP gene family was significantly increased in HCC samples compared to normal tissues, and the area under the curve (AUC) of GAR1, NHP2, NOP10, and DKC1 was 0.898, 0.962, 0.884, and 0.911, respectively. Increased expression of the H/ACA snoRNP gene family was associated with poor prognosis in HCC patients (Hazard Ratio, HR = 1.44 [1.02- 2.04], 1.70 [1.20- 2.40], 1.53 [1.09- 2.17], and 1.43 [1.02- 2.03], respectively; log-rank P = 0.036, 0.003, 0.014, 0.039, respectively). GO and KEGG analyses showed that co-expressed genes were primarily enriched in ribosome biogenesis. In addition, upregulated expression of H/ACA snoRNP gene family was related to the infiltration of various immune cells and multiple T cell exhaustion markers in HCC patients. Immunohistochemical analysis and Western blotting showed that the protein expression of H/ACA snoRNP gene family was higher in HCC tissues than in adjacent tissues of clinical samples.Conclusion: H/ACA snoRNP gene family expression was higher in HCC tissues than in normal or adjacent tissues and was highly associated with poor prognosis of HCC patients and, therefore, has the potential to serve as diagnostic and prognostic biomarkers for HCC.Keywords: hepatocellular carcinoma, H/ACA snoRNP gene family, diagnosis, prognosis, biomarker